Continuous User Verification in Cloud Storage Services using Deep Learning - burhan albayati (Academic Science Journal)
Cloud storage services have become a new paradigm for storing data user over the Internet. Users can access these services using a simple authentication login. This has led to increased potential attacks and misusing vital customer information. The behavior profiling technique has been successfully investigated as an additional intelligent security measure for continuous verification users after the simple login. A credible accuracy has been achieved when applying the method in a variety of applications such as telecommunication, credit card, and cloud services to detect and monitor misuse. To increase the accuracy of making a reliable decision, this paper proposes to combine two private datasets which are real-life user interactions with the desktop computer and Dropbox Cloud storage. The best experimental result achieved an EER of 3.6% based on applying a deep learning algorithm (CNN). This result indicates and encourages the feasibility of using behavioral profiling to protect cloud users from misuse.